2003
DOI: 10.1038/sj.onc.1206424
|View full text |Cite
|
Sign up to set email alerts
|

Data mining the p53 pathway in the Fugu genome: evidence for strong conservation of the apoptotic pathway

Abstract: The p53 tumour suppressor gene belongs to a small family of related proteins that includes two other members, p63 and p73. Phylogenetic and functional studies suggest that p63 and p73 are ancient genes that have essential roles in normal development, whereas p53 seems to have evolved more recently to prevent cell transformation. In mammalian cells, a plethora of proteins have been found to specifically regulate p53 activity. The genome of the fish Fugu rubripes has been recently published. It is the second ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…However, the regulation of p53 by Mdm2 may only exist in vertebrates, as so far researchers have failed to identify an Mdm2 homologue in either Drosophila or C. elegans. Analysis of the Fugu fish genome has revealed that although many of the p53 target genes such as PIG3 and PIDD, p53DINP1 are conserved, orthologues related to Fas, Bax, PUMA, Noxa and p53AIP were not found (Le Bras et al, 2003). This raises the interesting question as to which elements of the p53 response are conserved.…”
Section: Apoptosis: the Most Conserved Property Of P53mentioning
confidence: 94%
“…However, the regulation of p53 by Mdm2 may only exist in vertebrates, as so far researchers have failed to identify an Mdm2 homologue in either Drosophila or C. elegans. Analysis of the Fugu fish genome has revealed that although many of the p53 target genes such as PIG3 and PIDD, p53DINP1 are conserved, orthologues related to Fas, Bax, PUMA, Noxa and p53AIP were not found (Le Bras et al, 2003). This raises the interesting question as to which elements of the p53 response are conserved.…”
Section: Apoptosis: the Most Conserved Property Of P53mentioning
confidence: 94%
“…p53 has been cloned and characterised in several fish species and its importance during embryogenesis and DNA damage-induced apoptosis elicited by UV or by the anti-cancer compound camptothecin has been reported [125][126][127][128][129][130][131][132]. Moreover, data mining the p53 pathway in the Fugu genome has indicated conservation of the apoptotic pathway [133]. In this context, exposure of zebrafish embryos toirradiation was shown to induce substantial increase in p53-dependent activation of caspase-3 [98].…”
Section: Intrinsic Pathway In Fishmentioning
confidence: 97%
“…On the macro-scale, the challenging goal of Systems Biology is to integrate the different levels of information to explore the cellular complexity [72][73][74][75][76][77][78][79][80][81][82]. The aim is to combine available experimental and computational data to characterize the network of intermolecular interactions and their regulation.…”
Section: Conclusion and Outlook: Protein Interactions And Systems Bio...mentioning
confidence: 99%